(untitled) (Scientific journal of the Fergana State University, 2025)
Innovative pedagogical activity involves the introduction of new methods, technologies, and approaches into the educational process to improve the effectiveness of teaching and upbringing. The primary goal is to create conditions for the development of critical thinking, creative abilities, and students’ preparedness for a rapidly changing world. An important aspect of innovative pedagogy is the integration of modern information and communication technologies, the use of interdisciplinary approaches, and practice-oriented methods. This requires teachers to not only master new tools but also to adapt their professional activities, interaction with students, and the development of pedagogical culture.